Gas chromatography analysis of major free mono‐ and disaccharides in milk: Method assessment, validation, and application to real samples. Issue 23 (11th November 2016) - Idda, Ilenia; Spano, Nadia; Ciulu, Marco; Nurchi, Valeria M.; Panzanelli, Angelo; Pilo, Maria I.; Sanna, Gavino
Abstract : Saccharides are functional constituents of milk. Althoughd ‐lactose represents almost the totality of the saccharides in the milk, minor species, liked ‐glucose, d ‐galactose, myo ‐inositol and, as a result of severe thermal treatments, monosaccharides liked ‐tagatose, are also detectable. Although chromatography has been the main analytical approach used for accomplishing this task, quite surprisingly a validated gas chromatographic method aimed at the simultaneous determination of these compounds is still needed. Hence, our contribution is devoted to fill this gap. After the optimization of clean‐up and derivatization (conversion of saccharides in their trimethyl silyl ethers) steps, the adoption of a highly cross‐linked silphenylene stationary phase permitted to obtain high resolution and a fast chromatographic run. Validation was accomplished in terms of limit of detection, limit of quantification, linearity, precision, and trueness. The accuracy of the method was successfully tested on a number of partially skimmed milk samples. Excellent limits of detection for all analytes make this method eligible, also with respect to a gas chromatographic/mass spectrometry approach, for routine analysis and quality control in the dairy industries.